Actuators: Single‐Crystalline Vanadium Dioxide Actuators (Adv. Funct. Mater. 20/2019). (14th May 2019) - Shi, Run; Cai, Xiangbin; Wang, Weijun; Wang, Jingwei; Kong, Dejun; Cai, Nianduo; Chen, Pengcheng; He, Pingge; Wu, Zefei; Amini, Abbas; Wang, Ning; Cheng, Chun
Abstract : In article number1900527, Chun Cheng and co‐workers report an interesting single‐crystalline VO2 actuator that undergoes a unique self‐bending upon temperature change. This actuator is driven by a radially asymmetric domain behavior during the metal–insulator phase transition of a stoichiometry‐engineered VO2 nanobeam. The as‐fabricated nanobeam actuators show excellent actuation performance in various aspects and provide new ideas for the further development of microelectromechanical systems and microrobotics.